UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER PADA MATA PELAJARAN IPADI KELAS IV SDN NO 023905 BINJAI - SIMBOLON, RINCI (Jurnal Ilmiah Aquinas, 2019)
This research is Classroom Action Research (CAR). This study aims to determine the Improvement of learning outcomes and the implementation of learning using the NHT type cooperative learning model. The location of the study was carried out at SDN No. 023905 Binjai with the research subjects being class IV students 25 people. The time of the study is conducted in the odd semester of the 2018/2019. The research was conducted in two cycles. Data collection techniques used were tests and observation sheets. Observation results of the implementation of learning on the first cycle of teachers with a percentage of 60% with sufficient categories and the results of observation of the implementation of learning activities for students with a value of 68 with sufficient categories. The completeness of learning outcomes in cycle I was 15 students (60%), while students who did not complete were 10 students percentage (40%). In the second cycle the results of the observation of the implementation of learning on teachers with a percentage of 71.4% with good categories and observation of learning activities on students with a percentage of 80 with good categories. Student learning completeness in the second cycle was 22 students with a percentage (88%), while the ones that did not complete were 3 students with a percentage (12%). Based on the results of the analysis it can be concluded that there is an increase in learning outcomes using the cooperative type NHT model in grade IV SDN No. 023905 Binjai.